Analisis Faktor Eksternal Dan Internal Terhadap Pembiayaan Pada Bank Umum Syariah Yang Terdaftar Di OJK - Annisa Nadya; Marlina Tanjung; Sugianto Sugianto (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
This research is a quantitative study to determine the effect of inflation, BI interest rates, capital influences and problematic financing on financing at Islamic banks. The dependent variable in this study is financing. While the independent variables in this study are inflation, BI interest rates, capital, and problem financing. The population of this study is Sharia Commercial Banks registered with the Financial Services Authority, which amounts to 14 Banks. The sample selection uses non probability sampling. The data used are secondary data with panel data analysis method using e-views 10. The sample used was 14 Sharia Bank for the period of 2016-2018. The results of panel data regression with a significance level of 0.05 indicate that inflation, BI interest rates, and problematic financing have no effect on financing, and capital influences has effect on financing.